Cephalotoma patcharinae n. sp.—The First Record of Cephalotoma Species with a 2-Segmented Club of Antennae in the Oriental Region (Bostrichidae, Lyctinae: Trogoxylini) - Jerzy Borowski; Adam Byk; Sławomir Mazur; Tomasz Mokrzycki; Artur Rutkiewicz; Henryk Tracz; Agnieszka Ostrowska; Tomasz Oszako (Insects)
The paper presents a description of a new species of the genus Cephalotoma Lesne, caught in northern Thailand. The new species, C. patcharinae Borowski n. sp., is the first species in the Oriental region with a two-segmented club of antennae. The effect of the discussion presented in the paper is synonymising the tribe Cephalotomini Liu and Schönitzer, 2011 n. syn. with Trogoxylini Lesne, 1921. Moreover, the paper contains a key to classify all the species known from the Oriental region and belonging to the genus Cephalotoma.